Exploring the impact of sister city partnerships on emerging African cities - Isaac Kipkemoi; Gladys Khisa Sitati; Peter Kingori Gakai (Discover Cities)
Abstract Sister city relationships promise to serve as strategic mechanisms for fostering international cooperation and urban development, providing cities with avenues for economic growth, cultural enrichment, and global connectivity. This study examines the impact of sister city partnerships on Eldoret, a newly designated city in Kenya, assessing how these collaborations contribute to its modernization and global positioning while preserving its unique strengths. We analyze key thematic domains to evaluate the role of international networks in shaping Eldoret’s urban trajectory. Eldoret’s sister city agreements with Bad Vilbel, Indianapolis, Minneapolis, and Ithaca have enabled dynamic exchanges that reinforce the city’s strong athletic identity, agricultural significance, and manufacturing sector. Through comparative analysis, we investigate how these partnerships have supported cultural diplomacy, economic expansion, and institutional development in both Eldoret and its counterparts. Using GDP trends as an empirical marker, our findings indicate that post-partnership years account for approximately 37% of the variation in Eldoret’s GDP (R² = 0.37), with a positive slope estimate of USD 1.64 billion. We posit that integrating economic data with insights from established partnership models provides a robust framework for understanding how sister city connections influence urban development. By examining Eldoret’s unique positioning and engagement strategies, this study contributes to a broader discussion on the role of international collaborations in shaping the modernization pathways of new African cities.